Fracture behavior and damage mechanisms of sandstone subjected to wetting-drying cycles. (July 2020) - Cai, Xin; Zhou, Zilong; Tan, Lihai; Zang, Haizhi; Song, Zhengyang
Highlights: As the number of wetting-drying cycles increases, the density and P-wave velocity of sandstone gradually decrease and the porosity increases. The density and interconnectivity of the internal microcracks increase with wetting-drying cycles. Under the same loading rate, the fracture toughness and energy dissipation of rock decreases as the increasing cyclic number. The primary mechanisms for the rock deterioration after wetting-drying cycles are the dissolution of calcite and the intergranular cracking induced by clay swelling. Abstract: Rocks are usually subjected to cyclic wetting-drying due to the periodical changes in moist condition. To investigate the effect of wetting-drying cycles on the fracture behavior of sandstone, notched semi-circular bending tests were performed on sandstone samples after every ten cycles (a total of 50 cycles) under both quasi-static and dynamic loading conditions. Tests results indicate that both of fracture toughness and energy dissipation of sandstone significantly decrease with the increase of cycle number. Moreover, the microstructural characteristics reveal that after cyclic wetting-drying treatments, the calcite cementation between grains gradually dissolves and the density and width of inter-granular fracture increase, which could be responsible for the deterioration of rock mechanical properties.